Pro-environmental behavior–Renewable energy transitions nexus: Exploring the role of higher education and information and communications technology diffusion - Deshuai, Ma; Hui, Li; Ullah, Sana (Frontiers in Psychology, 2022)
The most accepted solution to deal with the problems of global warming and climate change is to transform the energy sector by moving toward renewable energy. Therefore, the primary focus of the analysis is to examine the role of renewable energy consumption, higher education, and ICT in improving environmental quality and green growth in China. We have employed the quantile ARDL model to obtain the short-and long-run estimates. According to the findings of QARDL, the long-run estimated coefficients of renewable energy consumption and higher education are positively significant in most quantiles. However, in the long run, the estimates attached to ICT are insignificant in the CO2 emissions model in most quantiles. On the other hand, the estimates of renewable energy consumption are significantly positive from the 50th quantile and onward in the green growth model, confirming that the higher the renewable energy in the economy, closer it will get to the target of green economic growth. The long-run estimates of higher education and ICT are positively significant at most quantiles in the green growth model. In the short run, renewable energy consumption turned out to be the most critical determinant of CO2 emissions and green growth.